Modeling the Mechanical Properties of Functionalized Carbon Nanotubes and Their Composites: Design at the Atomic Level - Qing-Sheng Yang; Bing-Qi Li; Xiao-Qiao He; Yiu-Wing Mai (Advances in Condensed Matter Physics)
This investigation focuses on the design of functionalization configuration at the atomic level to determine the influence of atomic structure on the mechanical properties of functionalized carbon nanotubes (F-CNTs) and their composites. Tension and compressive buckling behaviors of different configurations of CNTs functionalized by H atoms are studied by a molecular dynamics (MD) method. It is shown that H-atom functionalization reduces Young’s modulus of CNTs, but Young’s modulus is not sensitive to the functionalization configuration. The configuration does, however, affect the tensile strength and critical buckling stress of CNTs. Further, the stress-strain relations of composites reinforced by nonfunctionalized and various functionalized CNTs are analyzed.